Originales e inéditos, 1928, José Carlos Mariátegui - Melgar , Ricardo; Pásara , Manuel (Ariadna Ediciones, 2018)
Review and update of texts by Peruvian JC Mariátegui and its importance for the political and editorial history of Latin America